Design of Network Middle-Ware Base on Flash Streaming Media - Jian Huang; Xiaopei Liu; Hongmei Yan (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper analyzes the main information and streaming media service function of Real Time Messaging Protocol for Flash media remote play. It simplifies and achieves the Flash AV network live broadcast, network broadcasting and releasing function, which can support to operate in the cross-platform of Windows, Linux and embedded system with good property by the cross-platform testing. Meanwhile, it supports to connect with FMP seamlessly, being widely applied in the AV server of Windows, Linux platform or the network AV electronic products of embedded platform connecting with FMP seamlessly. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3525